2013
DOI: 10.1007/s12576-013-0278-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of muscle temperature stimulates muscle glucose uptake in vivo and in vitro

Abstract: The purpose of this study was to examine whether elevation of muscle temperature per se might be a stimulatory factor to increase muscle glucose uptake. Heat stimulation to rat hindlimbs increased glucose uptake measured in vivo in the extensor digitorum longus (EDL) and soleus muscles with a significant increase in muscle temperature. This thermal effect was observed again when glucose uptake was measured in vitro in both isolated muscles immediately after the heat stimulation in vivo. When heat stimulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Therapeutic effects of heat stress on insulin resistance have been reported in type 2 diabetes of rodents (hindlimb hot bathing, 41ºC, 20 min) 5) and patients (Hot tub bathing, 37.8-41.0ºC, 30 min/ day, 6 days/week, 3 weeks) 6) , mediated by up-regulated glucose uptake in skeletal muscles, based on a mechanistic study investigating isolated skeletal muscle (42ºC, 30 min) 7) . In addition to glucose metabolism, several lines of evidence demonstrated various adaptabilities of mitochondria-centered oxidative metabolism by heat stress.…”
Section: Brief History Of Research On Heat Stress In Skeletal Musclementioning
confidence: 99%
“…Therapeutic effects of heat stress on insulin resistance have been reported in type 2 diabetes of rodents (hindlimb hot bathing, 41ºC, 20 min) 5) and patients (Hot tub bathing, 37.8-41.0ºC, 30 min/ day, 6 days/week, 3 weeks) 6) , mediated by up-regulated glucose uptake in skeletal muscles, based on a mechanistic study investigating isolated skeletal muscle (42ºC, 30 min) 7) . In addition to glucose metabolism, several lines of evidence demonstrated various adaptabilities of mitochondria-centered oxidative metabolism by heat stress.…”
Section: Brief History Of Research On Heat Stress In Skeletal Musclementioning
confidence: 99%
“…Short-term HS at 41°C for 20 min enhanced insulin-dependent glucose uptake in rat skeletal muscles 6) . Furthermore, HS at approximately 42°C for approximately 30 min stimulated insulin-independent glucose uptake, which was accompanied by energy depletion in rat skeletal muscles 7,8) . This HS-induced stimulation of glucose uptake was abrogated by an AMPK inhibitor 7,8) .…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, HS at approximately 42°C for approximately 30 min stimulated insulin-independent glucose uptake, which was accompanied by energy depletion in rat skeletal muscles 7,8) . This HS-induced stimulation of glucose uptake was abrogated by an AMPK inhibitor 7,8) . Therefore, these results suggested that HS enhances skeletal muscle glucose utilization via an AMPK-dependent mechanism.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…An elegant study demonstrated in animal models that the simple increase of skeletal muscle temperature is able to stimulate glucose uptake through the activations of AMPK and Akt, which were partially reversed after the use of pharmacological inhibitors of these proteins, such as compound C and Wortmannin, respectively 60 . Other studies also suggested that the increased glucose uptake, which occurs because of increase in muscle temperature, is due to the increased production of reactive oxygen species (ROS) that regulates the activity of NOS (promoting NO production) favoring the formation of RNS (as a result of the reaction of NO with ROS previously exposed).…”
Section: Muscle Temperature and Glucose Uptakementioning
confidence: 99%